The DANUBIUS-RI supersite of Po delta and North Adriatic Lagoons: a living lab on transitional environments in the Adriatic Sea - Francesca De Pascalis; Emilio Urbinati; Ali Aalifar; Leslie Aveytua Alcazar; Luca Arpaia; Marco Bajo; Andrea Barbanti; Francesco Barbariol; Mauro Bastianini; Debora Bellafiore; Federico Bellati; Alvise Benetazzo; et al. (Estuarine, Coastal and Shelf Science, 2025)

High-resolution satellite turbidity and sea surface temperature observations of river plume interactions during a significant flood event - V. E. Brando; F. Braga; L. Zaggia; C. Giardino; M. Bresciani; E. Matta; D. Bellafiore; C. Ferrarin; F. Maicu; A. Benetazzo; D. Bonaldo; F. M. Falcieri; et al. (Ocean Science, 2015)
Sea surface temperature (SST) and turbidity (T) derived from Landsat 8 (L8) imagery were used to characterize river plumes in the northern Adriatic Sea (NAS) during a significant flood event in November 2014. Circulation patterns and sea surface salinity (SSS) from an operational coupled ocean-wave model supported the interpretation of the plumes' interaction with the receiving waters and among them. There was a good agreement of the SSS, T, and SST fields at the sub-mesoscale and mesoscale delineation of the major river plumes. L8 30 m resolution also enabled the description of smaller plume structures. The different plumes' reflectance spectra were related to the lithological fingerprint of the sediments in the river catchments. Sharp fronts in T and SST delimited each single river plume. The isotherms and turbidity isolines' coupling varied among the plumes due to differences in particle loads and surface temperatures in the discharged waters. The surface expressions of all the river plumes occurring in NAS were classified based on the occurrence of the plume dynamical regions in the L8 30 m resolution imagery.

Impact of subthalamic nucleus stimulation on the initiation of gait in Parkinson’s disease - P. Crenna; I. Carpinella; M. Rabuffetti; M. Rizzone; L. Lopiano; M. Lanotte; M. Ferrarin (Experimental Brain Research, 2006)

Procedure for the quantitative evaluation of motor disturbances in cerebellar ataxic patients - M. Ferrarin; M. Gironi; L. Mendozzi; R. Nemni; P. Mazzoleni; M. Rabuffetti (Medical & Biological Engineering & Computing, 2005)

Effects of bilateral subthalamic stimulation on gait kinematics and kinetics in Parkinson?s disease - M. Ferrarin; M. Rizzone; B. Bergamasco; M. Lanotte; M. Recalcati; A. Pedotti; L. Lopiano (Experimental Brain Research, 2005)

Microprocessor-controlled optical stimulating device to improve the gait of patients with Parkinson's disease - M. Ferrarin; M. Brambilla; L. Garavello; A. Di Candia; A. Pedotti; M. Rabuffetti (Medical & Biological Engineering & Computing, 2004)

Touch-screen system for assessing visuo-motor exploratory skills in neuropsychological disorders of spatial cognition - M. Rabuffetti; M. Ferrarin; R. Spadone; D. Pellegatta; V. Gentileschi; G. Vallar; A. Pedotti (Medical & Biological Engineering & Computing, 2002)

Standing-up exerciser based on functional electrical stimulation and body weight relief - M. Ferrarin; E. E. Pavan; R. Spadone; R. Cardini; C. Frigo (Medical & Biological Engineering & Computing, 2002)

Spot check of the calibrated force platform location - M. Rabuffetti; M. Ferrarin; F. Benvenuti (Medical & Biological Engineering & Computing, 2001)

Analysis of thermal properties of wheelchair cushions with thermography - M. Ferrarin; N. Ludwig (Medical & Biological Engineering & Computing, 2000)